Dissecting genetics of cutaneous miRNA in a mouse model of an autoimmune blistering disease. (December 2016) - Gupta, Yask; Möller, Steffen; Witte, Mareike; Belheouane, Meriem; Sezin, Tanya; Hirose, Misa; Vorobyev, Artem; Niesar, Felix; Bischof, Julia; Ludwig, Ralf; Zillikens, Detlef; Sadik, Christian; et al.
Abstract Background MicroRNAs (miRNAs ) are small endogenous non-coding RNAs that control genes at post-transcriptional level. They are essential for development and tissue differentiation, and such altered miRNA expression patterns are linked to the pathogenesis of inflammation and cancer. There is evidence that miRNA expression is genetically controlled similar to the transcription of protein-coding genes and previous studies identified quantitative trait loci (QTL) for miRNA expression in the liver. So far, little attention has been paid to miRNA expression in the skin. Moreover, epistatic control of miRNA expression remains unknown. In this study, we characterize genetic regulation of cutaneous miRNA and their correlation with skin inflammation using a previously established murine autoimmune-prone advanced intercross line. Results We identifiedin silico 42 eQTL controlling the expression of 38 cutaneous miRNAs and furthermore found two chromosomal hot-spots on chromosomes 2 and 8 that control the expression of multiple miRNAs. Moreover, for 8 miRNAs an interacting effect from pairs of SNPs was observed. Combining the constraints on genes from the statistical interaction of their loci and further using curated protein interaction networks, the number of candidate genes for association of miRNAs was reduced to a set of several genes. A cluster analysis identified miR-379 and miR-223 to be associated with EBA severity/onset, where miR-379 was observed to be associated to loci on chromosome 6. Conclusion The murine advanced intercross line allowed us to identify the genetic loci regulating multiple miRNA in skin. The recurrence of trans-eQTL and epistasis suggest that cutaneous miRNAs are regulated by yet an unexplored complex gene networks. Further, using co-expression analysis of miRNA expression levels we showed that multiple miRNA contribute to multiple pathways that might be involved in pathogenesis of autoimmune skin blistering disease. Specifically, we provide evidence that miRNA such as miR-223 and miR-379 may play critical role in disease progression and severity.